Pajak Kekayaan, Alternatif Sumber Penerimaan Pajak di Indonesia Merespons Pandemi Covid-19 - Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2022)
In response to the decline in tax revenue due to the Covid-19 pandemic, the government has issued a regulation to collect a new tax, namely the Carbon Tax through Law Number 7 of 2021 concerning Harmonization of Tax Regulations. Because this Carbon Tax is being implemented for the first time in Indonesia and its calculation is also not simple, it is estimated that the successful collection of it will take a long time. Whereas the need to explore new sources of tax revenue is needed at this time in the short term to cope with sharply increasing expenditures in order to overcome the medical and social impacts of the Covid-19 pandemic. The government could consider implementing a Wealth Tax in addition to existing taxes including the Carbon Tax. Wealth Tax in addition to increasing tax revenues can also be used as a means of redistribution of wealth in order to reduce the wide gap between the rich and the poor. The proposed Wealth Tax is a Wealth Tax that is levied only once, intended for individuals, with a threshold as well as Non-Taxable Wealth (NTW) of Rp21,000,000,000.00 for unmarried taxpayers and Rp22,500,000,000.00 for marriage taxpayers, using progressive rates of 0.2%, 0.4%, 0.6%, and 0.75%, and can be repaid in installments for 5 years. The basis for imposition of Wealth Tax is net assets, namely the total assets minus the total liabilities reported in the Annual Income Tax Return (SPT) of the previous year's individual taxpayers minus the Non-Taxable Wealth (NTW). Using data on the wealth of the Indonesian population in 2018, it is estimated that thecollection of this Wealth Tax can generate additional tax revenues of around 0.83% of the Gross Domestic Product in 2020.